HERIC Inverter- A SEPIC based transformer-less converter design and simulation for isolated standalone PV system. Issue 1 (September 2020) - Udayakumar, M.D.; Gowthaman, K.S.; Prabhu, A; Nazar Ali, A.
Abstract: Photovoltaic transformer-less inverter due to its high efficiency, low power loss and cost plays an important role in energy market. In this paper solar PV based 1φ transformer-less HERIC converter for standalone isolated PV system has been designed and analysed. To control the solar PV output, a dc-dc SEPIC converter is modelled and designed with the feature of Maximum Power Point Tracking. Contrary to other inverter topologies H5, H6, NPC (neutral point clamping), HERIC inverter comprises low leakage current. The entire proposed system is designed and simulation is carried out in MATLAB environment.